2020
DOI: 10.1016/j.enbuild.2020.110408
|View full text |Cite
|
Sign up to set email alerts
|

Building commissioning costs and savings across three decades and 1500 North American buildings

Abstract: Building commissioning (Cx) is a process for assuring efficient building operations that can be applied to new construction and existing buildings, resulting in energy and non-energy benefits. Quantifying the benefits of commissioning is challenging, but a 2009 study of 643 commercial buildings provided a solid initial data set to which we added 839 additional buildings for a significantly expanded and updated meta-analysis representing 34.7 million square meters (373 million square feet) of floor area. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Building commissioning was reported to provide greater benefits, especially in high-tech buildings. Crowe et al [34] quantified the benefits of building commissioning by extending the data set of a previously conducted study. The savings varied between 3% and 16% depending on the project type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building commissioning was reported to provide greater benefits, especially in high-tech buildings. Crowe et al [34] quantified the benefits of building commissioning by extending the data set of a previously conducted study. The savings varied between 3% and 16% depending on the project type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EEMs identified and implemented through use of building analytics tools should be consistent with the measures identified in existing building commissioning (EBCx) projects. Therefore, the study used the median EEMs implementation cost from a recent EBCx study across three decades and 1,500 buildings [25] as an estimation of C EEM . The EBCx study documented common EEM implementation costs as approximately one-third of the entire EBCx cost.…”
Section: Simple Payback Periodmentioning
confidence: 99%
“…The tune-ups target low-and no-cost actions related to building operations and maintenance. Several studies have shown that savings from building commissioning can yield savings in the range of 5-15%, with simple paybacks of 0.8-3.5 years (Crowe et al 2020;Mills 2011;Mills & Mathew 2014).…”
Section: Seattle's Policy Frameworkmentioning
confidence: 99%